Ethanolic extract of Schizonepeta tenuifolia attenuates osteoclast formation and activation in vitro and protects against lipopolysaccharide-induced bone loss in vivo. Issue 1 (December 2016) - Kim, Ju-Young; Baek, Jong; Ahn, Sung-Jun; Cheon, Yoon-Hee; Park, Sun-Hyang; Yang, Miyoung; Choi, Min; Oh, Jaemin
Abstract Background Excessive osteoclast activity is a major cause of metabolic bone disorders, such as osteopenia, rheumatoid arthritis, and osteoporosis. Thus, discovery of agents targeting osteoclast differentiation and bone resorption is important for development of novel treatments for bone diseases. It has been demonstrated that ethanolic extract ofschizonepeta tenuifolia (EEST) has potent anti-oxidant and anti-inflammatory activities. However, the beneficial effects of EEST on bone metabolism have not been studied. Therefore, we intend to investigate the effects of EEST on osteoclast differentiation. Methods We examined the effects and mechanisms of action of the EEST on osteoclastogenesis in vitro in bone marrow macrophages (BMMs) stimulated with receptor activator of nuclear factor kappa-B ligand (RANKL) and in vivo using a mouse model of lipopolysaccharide (LPS)-induced bone destruction. Results We found that EEST inhibited phosphorylation of Akt and IkB at early stages of RANKL-induced osteoclastogenesis. Furthermore, EEST negatively controlled the transcription and translation levels of nuclear factor of activated T cells c1 (NFATc1) and the translation level of c-Fos at the final stage of osteoclast differentiation. Reflecting these effects, EEST blocked both filamentous actin (F-actin) ring formation and bone resorbing activity of mature osteoclasts in vitro. The inhibitory effects of EEST on osteoclast formation and activity were observed in an LPS-mediated bone erosion mouse model using micro-CT and histological analysis. Conclusions EEST is a potential agent that is able to treat osteoclast-related bone diseases, such as osteoporosis.